Tempo de reação discriminativo em atletas de futebol: comparações por categoria e tabelas de referência - Hebert Soares Bernardino (2018)
The discriminative reaction time can be defined as the time between the moment of presentation of the external stimulus to the beginning of the motor response, in which different stimuli are presented and one or more responses can be correct, after the reaction we have the time of movement that is the time spent by the individual to perform the motor action. To better understand the capabilities in soccer athletes of the youth teams are objectives of this study: (a) to propose a table of the discriminative reaction time; (b) proposing a reference time-of-motion table; (c) comparing the discriminative reaction time in soccer athletes between the base categories; (d) comparing the movement time in soccer athletes between the base categories. The study included 314 athletes participated from three teams from Minas Gerais State, composed by the following youth teams: U-14 (n = 75), U-15 (n = 64), U-17 (n = 97), and U-20 (n = 78). The instruments used were: (a) a demographic data questionnaire, and (b) Vienna test System SPORTS@ to evaluate the discriminative reaction time of the athletes using the Reaction Test (RT/S5). We used for statistical analysis: descriptive statistics, inferential statistics, effect size (ES) and significance test and Cronbach's α. The statistical procedures were calculated using SPSS® (Statistical Package for Social Science) version 23.0, with significance level given by p<0.05. The results showed that Cronbach's α values were satisfactory for the dimensions of discriminative reaction time and movement time in youth teams (α>0.70). The results for the mean discriminative reaction time observed in the youth teams were U-14 (552 ms ± 62.61), U-15 (533 ms ± 61.13), U-17 (526 ms ± 65.37), and U-20 (548 ms ± 61.35). When comparing this variable between the youth teams, there was a difference between U-14 and U-17 youth teams (p = 0.03) with small effect size (0.19); no statistically significant difference was found in the remaining comparisons. For the time of movement, the averages found were: U-14 (154 ms ± 46.97), U-15 (147 ms ± 42,25), U-17 (147 ms ± 42,72), and U-20 145 ms ± 35.96); that is, the responses for this variable are similar between the youth teams. The results of the reference table are classified in percentiles of 1 to 99 and are presented by the responses in the discriminative reaction time and in the time of movement for the youth soccer teams. It is concluded that the reference table will allow to define reliable parameters in the evaluation of discriminative reaction time and movement time for soccer players of the U-14, U-15, U-17 and U-20 youth teams. Furthermore, it is concluded that despite the difference found in the reaction time of soccer players between sub-14 and sub-17 youth teams, no differences were identified in the other comparisons, which leads us to conclude that this variable has a behavior stable during the entire training process of the athletes.